Simple PI fuzzy logic controller applied in DC-AC converter - Ayob, S. M.; Salam, Zainal; Azli, N. A. (2006)
In this paper, a simple proportional integral fuzzy logic controller (PI-FLC) applied to a DC-AC converter is presented. This approach uses signed distance method, where the multiinput single output (MISO) system can be reduced to single input single output (SISO) system without degrading the original performance of MISO PI-FLC system. The input-output relationship of SISO PI-FLC system then can be simply mapped using piecewise linear approximation. A comparison with the original PI-FLC is carried out by MATLAB-Simulink simulation to verify the performance of the proposed approach